2018
DOI: 10.1039/c7cp06594a
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure glass formation of a series of 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide homologues

Abstract: We investigated the stability of the liquid phase of a series of 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([Cmim][TFSI]) homologues with different alkyl chain lengths for 3 ≤ n ≤ 10 at room temperature. We found that all [Cmim][TFSI] samples (n = 3-10) formed a glassy state when pressure was applied. Intriguingly, the glass transition pressure (p) slightly increases up to n = 5, reaches a plateau at n ≧ 8, and increases again at n = 10. This is completely different from the high-pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“… 7 , 29 , 33 While the length scale of the apolar domains, defined by the position of a low Q peak in the static structure factor, follows the trend of the overall density change, the intensity of the peak decreases with increasing temperature and increasing pressure. 23 , 31 33 With increased temperature, the driving force for segregation into apolar domains is decreased, whereas conformational changes of the alkyl side chains have been suggested to be responsible for the collapse of the domains at a high pressure, >2 GPa. 32 The position of the charge ordering peak has also been shown to follow the density as a function of temperature but with a weaker dependence.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 29 , 33 While the length scale of the apolar domains, defined by the position of a low Q peak in the static structure factor, follows the trend of the overall density change, the intensity of the peak decreases with increasing temperature and increasing pressure. 23 , 31 33 With increased temperature, the driving force for segregation into apolar domains is decreased, whereas conformational changes of the alkyl side chains have been suggested to be responsible for the collapse of the domains at a high pressure, >2 GPa. 32 The position of the charge ordering peak has also been shown to follow the density as a function of temperature but with a weaker dependence.…”
Section: Introductionmentioning
confidence: 99%
“…57 Figure 1 shows then the pressure dependence (from ambient pressure to 2.5 GPa) of a portion (Q < 20 nm −1 ) of the computed X-ray diffraction pattern; in the inset, the published data by Yoshimura et al for the same RTIL are shown [note that these data sets cover a more limited Q range (Q < 5 nm −1 )]. 44 The computed patterns show three diffraction features centred at approximately Q 1 = 3.5, Q 2 = 8, and Q 3 = 13 nm −1 : they have been related to polarity, charge, and adjacency alternations, respectively. [17][18][19] It is noteworthy that, similarly to the experimental data, the peak centred at Q 1 slightly decreases its amplitude when passing from ambient to 0.68 GPa but then maintains essentially unaltered upon further pressurization (we also stress the fact that experimental patterns do not show indication of the appearing of Bragg peaks that might indicate an amorphous-crystalline phase transition over the probed pressure range).…”
mentioning
confidence: 99%
“…Pressure changes allow investigating intermolecular interactions, by inducing density changes without introducing the chaotic perturbation that temperature changes induce. As a matter of fact, while temperature dependence studies of morphology in RTILs have been reported in the past, 13,15,31 the pressure dependence of the mesoscopic organization in aprotic RTILs has been explored by means of experimental X-ray studies [42][43][44] and simulations [45][46][47][48][49][50] 42 Therein the progressive position shift and amplitude vanishing of the low Q peak centred at ca. 3 nm −1 had been observed.…”
mentioning
confidence: 99%
See 2 more Smart Citations